Dysglycemia screening with oral glucose tolerance test in adolescents with polycystic ovary syndrome and relationship with obesity - Jyotsna Gupta; Zoltan Antal; Elizabeth Mauer; Linda M. Gerber; Anjile An; Marisa Censani (BMC Endocrine Disorders, 2022)
Abstract Background Adolescents with polycystic ovary syndrome (PCOS) are at increased risk of impaired glucose tolerance (IGT) and type 2 diabetes mellitus. The aim of this study is to evaluate dysglycemia and biochemical differences based on BMI status and assess the prognostic ability of elevated hemoglobin A1c (HbA1c) in predicting an abnormal 2 hour oral glucose tolerance test (OGTT). Methods Retrospective cohort of female patients aged 11-18 years who underwent 75-g OGTT and were evaluated for PCOS at an urban tertiary care hospital between January 2002 to December 2017. Results In 106 adolescents with PCOS who had OGTT results available, IGT was markedly pronounced in the ≥95th percentile BMI group (17 out of 72; 23.6%) compared with <95th percentile BMI group (4 out of 34; 11.7%). One patient with obesity met the criteria for type 2 diabetes. Patients with obesity had significantly higher homeostasis model assessment (HOMA-IR) and lower whole body insulin sensitivity index (WBISI) (p < 0.001) compared to patients without obesity. Free testosterone levels were also higher in patients with obesity (p< 0.03) and were significantly associated with HOMA-IR when controlling for body mass index (BMI). HbA1c did not demonstrate a strong ability to predict abnormal OGTT on receiver operating characteristic (ROC) curve analysis [Area under the curve (AUC) = 0.572, 95% CI: 0.428, 0.939]). Conclusions In a study to assess glucose abnormalities in adolescents with PCOS, IGT was found to be markedly increased in patients with obesity, with abnormal glucose metabolism identified in over one-fifth of the patients. HbA1c alone may be a poor test to assess IGT and we recommend that adolescents diagnosed with PCOS and obesity undergo formal oral glucose tolerance testing.